The impact of the war in Syria on female workforce during the period from 1990 to 2018 - محمد أسامة; حليوه ليلى (Latakia University Journal - Arts and Humanities Sciences Series, 2021)
The women decision about to go out to work is one of the most important and difficult decisions, especially in the societies of the third world countries, and this decision has many social and economic consequences, and the decision of going out to work is subject to many influencing factors that differ from one society to another. This research studies the impact of the war in Syria on the female workforce in Latakia in particular. And it reached too many results, the most important of which are: - There are substantial differences of statistical significance between the numbers of the female force in the Latakia city before and after the war. - There are substantial differences of statistical significance between the numbers of women working in the government sector before and after the war. - There are no significant statistical differences between the numbers of women working in the private sector before and after the war. - There are substantial differences of statistical significance between the rates of economic activity in the Latakia city before and after the war.